A PERBANDINGAN HUKUM TENTANG MAHKAMAH KONSTITUSI INDONESIA DENGAN MAHKAMAH KONSTITUSI BELGIA - Haryokusumo Nugroho Putro; Ferry Edwar (Fakultas Hukum Universitas Trisakti, 2023)
The concept of testing norms through a judicial institution is known as a judicial review. The doctrine of Judicial review differs from country to country. The development of judicial review in Belgium has almost the same as in Indonesia. The problem is what are the differences and similarities Judicial review by the Constitutional Court of the Indonesia and Constitutional Arbitrage in Belgium? What are the advantages/disadvantages of Judicial review by the Constitutional Court of the Republic of Indonesia and Constitutional Arbitrage in Belgium? The results of the study show that the application of judicial review by the Constitutional Court in Indonesia and in Belgium has similarities as well as differences. The advantages and disadvantages between the Judicial review by the Constitutional Court of the Republic of Indonesia and Constitutional Arbitrage in Belgium, can be used as material for evaluating the judicial review system in the Republic of Indonesia in order to create a better legal system and provide benefits to society. Discussion and conclusion that the Similarities and Differences of judicial review in Indonesia and Belgium are institutions authorized to carry out judicial reviews; Authority examines Government actions; Submission of judicial review. The advantage of judicial review is that there is no interference from other parties such as the Court, the Government or the People's Representative Council. Lack of judicial review, there are two judicial institutions that have the authority to handle judicial.